ANALYSIS OF NORMATIVE REQUIREMENTS FOR THE RESULTS OF PROFESSIONAL TRAINING OF MATHEMATICS AND COMPUTER SCIENCE TEACHERS IN THE CONTEXT OF THEIR TRAINING FOR THE USE OF VIRTUAL VISUALIZATION TOOLS - Mulesa, Pavlo (Physical and Mathematical Education, 2022)
Formulation of the problem. For future teachers of mathematics and informatics, a situation is emerging in which it is necessary to learn to make qualified decisions regarding the possibilities of effective use of virtual visualization tools in professional activities and to select and forecast the necessary digital technologies for their use in professional activities. Materials and methods. Theoretical methods of scientific knowledge (content analysis of documents of normative and legal provision of education informatization, Internet resources; theoretical analysis and generalization of scientific research in the field of education in Ukraine). Results. Based on the analysis of educational programs, curricula, and work programs, it should be stated that the activities of higher education institutions to prepare future teachers of mathematics and informatics for the use of virtual visualization tools in professional activities are not systematic, they are carried out spontaneously and in a fragmented manner. At the same time, it is worth noting that at the level of administration and graduation departments, awareness of the importance of preparing future teachers of mathematics and computer science to use virtual visualization tools in their professional activities is being pursued through the updating of educational programs, the introduction of separate special courses and variable disciplines, and the internationalization of the institution’s educational activities. At the same time, informatics disciplines occupy a small part of the educational load (12%); curricula contain approximately the same IT disciplines (sometimes they are grouped into one course), which indicates their similarity; about 50% of the educational load in informatics disciplines is allocated to classroom work (lectures and laboratory classes); 56% of the total educational time planned for informatics disciplines is allocated to independent work of students. Conclusions. The conducted analysis provides grounds for the conclusion that a high level of training for future teachers of mathematics and informatics for the use of virtual visual aids in professional activities cannot be ensured within the limits of the existing professional training. The theoretical justification and implementation of a pedagogical system of training future teachers of mathematics and computer science in higher education institutions for the use of virtual visualization tools in professional activities are appropriate for further research.